Practising Interdisciplinarity - Weingart, Peter; Stehr, Nico (Book collections on Project MUSE., 2000)
First-hand insights into the operations and successes of some of the world's foremost interdisciplinary research centres and the ways in which interdisciplinarity is researched, organized, and taught around the world.